THE RUTHENIAN COURTS OF THE RURIK DYNASTY PRINCESSES IN THE LANDS OF THE PIAST DYNASTY IN THE 11TH CENTURY: THE ATTEMPT OF THE SEARCHING AND RECONSTRUCTION - VOLOSHCHUK, MYROSLAV (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The gradual Christianization of the major dynasties of so-called ‘Younger Europe’ resulted, among other things, in the activization of their matrimonial policy. Throughout Middle Ages, the most active in this regard were the Rurik and the Piast dynasties. The tradition of bilateral marriage relations among the ruling houses of Europe was established in the early 11th century and uninterruptedly continued into the mid-14th century. In the 11th century, there were registered 7 princely marriages; four of them, in Poland – three Ruthenian brides were given in marriage to the representatives of the Piast dynasty; besides, there was one case of concubinage. Two of the marriages were fertile: altogether, six children were born (five boys and a girl). One marriage proved to be infertile. On her way to her husband’s land, each Ruthenian bride was accompanied by an escort consisting chiefly of women; but there had to be some men too, a personal confessor and spiritual advisor in particular. Supposedly, their main function was to prepare the princesses for marriage; later, those persons composed their ladies’ own courts, varying in quantity and duration, within the greater courts of their husbands. In this article, I focus on the quest for probable Ruthenians within the inner circles of the Rurik dynasty princesses married into the Piast dynasty in the 11th century. The main challenges of the quest are the insufficiency of the 11th – the early 12th-century historical sources and the inaccuracy of the late medieval materials on the subject, whose evidence requires critical view and verification. Thus it appears to be almost impossible to establish the names of all those persons who accompanied the Ruthenian princesses to the Piasts’ lands, though their presence can be inferred from historical narratives.